Tools for Co-expressing Multiple Proteins in Mammalian Cells - Assur, Zahra (2012)
Structural and functional studies of many mammalian systems are critically dependent on abundant supplies of recombinant multi-protein complexes. Mammalian cells are often the most ideal, if not the only suitable host for such experiments. This is due to their intrinsic capability to generate functional mammalian proteins. This advantage is frequently countered by problems with yields in expression, time required to generate over-expressing lines, and elevated costs. Co-expression of multiple proteins adds another level of complexity to these experiments, as cells need to be screened and selected for expression of suitable levels of each component. Here we present an efficient fluorescence marking procedure for establishing stable cell lines that over-express two proteins in co-ordination, and we validate the method in the production of recombinant monoclonal antibody Fab fragments. This procedure may readily be expanded to systems of greater complexity, comprising more then two components.